P-048 YI Prevalence of Concomitant Inflammatory Bowel Disease and Irritable Bowel Syndrome Between Hispanics and Non-Hispanic Whites (NHW). (March 2016) - Szeto, Winnie; MaDireddy, Naga Krishnakanth; Tamariz, Leonardo; Abreu, Maria; Moshiree, Baharak
Abstract : Background: Inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) can occur concomitantly. Non- white IBS patients have been shown to experience impairment in vitality and role limitations (Gralnek et al. J Clin Gastroenterol. 2004;38(9):782–9). Furthermore, our group has demonstrated phenotypical differences between races in IBD presentation. The aim of our study is to report the prevalence of IBD, IBS or both diseases in minorities and non-minorities in the state of Florida. Methods: We conducted a cross-sectional analysis of all ambulatory and hospital discharge diagnoses during 2009 in Florida. We identified all subjects with IBD, IBS or both, using International Classification of Diseases, 9th Revision codes along with the race/ethnicity of each individual. The prevalence of each disease by ethnicity was then calculated. Results: We identified 36, 602 subjects with IBD (n = 19, 012), IBS (n = 17, 590) or both diagnoses (n = 377). Of the IBD patients, 10% were NHW, 81% Black and 9% Hispanic. In the IBS cohort, 6% were NHW, 87% Black and 6% Hispanic while in the concomitant IBD and IBS population 8% were NHW, 84% Black and 7% Hispanic. The mean age was 56 ± 20, 69% were female and a Charlson score of 1.25 ± 1.80 was found. Fifty percent of the cohort had IBD and 16% were minorities. 2.1% of IBS patients were found to have concomitant IBD while 1.9% of IBD patients were found to have concomitant IBS. Conclusions: IBS and IBD are uncommonly reported as concomitant diseases. IBS is less prevalent in minorities than IBD in our cohort. When IBS and IBD present together the racial distribution is similar to that of IBD. Future studies should focus on evaluating the racial differences between these common gastrointestinal diseases. In addition, further studies should be done to evaluate confounding factors and morbidities related to patients with IBD and co-existent IBS across ethnicities.